2012
DOI: 10.1089/rej.2012.1346
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Dietary Extra-Virgin Olive Oil Rich in Polyphenols Reverses Age-Related Dysfunctions in Motor Coordination and Contextual Memory in Mice: Role of Oxidative Stress

Abstract: The aim of this study was to evaluate the effects of olive oil phenols on brain aging in mice and to verify whether the antioxidant and antiinflammatory activities of these polyphenols were involved. C57Bl/6J mice were fed from middle age to senescence with extra-virgin olive oil (10% wt/wt dry diet) rich in phenols (total polyphenol dose/day, 6 mg/kg). Behavioral tests were employed to assess cognitive, motor, and emotional behavior after 6 or 12 months of treatment. Parameters of oxidative status and inflamm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 65 publications
(41 citation statements)
references
References 48 publications
1
39
0
Order By: Relevance
“…EVOO was purchased from Cipolloni and Petesse S.p.A. (Foligno, Perugia, Italy). The analysis of the phenolic content and the preparation of the rectified olive oil (ROO), devoid of phenolic compounds, was performed in the laboratory of Prof. Servili, Department of Food Sciences, University of Perugia, Italy, as previously reported [16]. …”
Section: Methodsmentioning
confidence: 95%
“…EVOO was purchased from Cipolloni and Petesse S.p.A. (Foligno, Perugia, Italy). The analysis of the phenolic content and the preparation of the rectified olive oil (ROO), devoid of phenolic compounds, was performed in the laboratory of Prof. Servili, Department of Food Sciences, University of Perugia, Italy, as previously reported [16]. …”
Section: Methodsmentioning
confidence: 95%
“…Previous studies have shown that consumption of EVOO results in amelioration of learning and memory in SAMP8 mice, and a reversal of age‐related dysfunctions in old mice 8, 9, 10. In both cases, the authors attributed those beneficial effects to the EVOO phenolic compounds and their antioxidant ability to protect against the disease‐related and age‐associated brain oxidation of these animals 8, 9, 10.…”
Section: Introductionmentioning
confidence: 96%
“…In both cases, the authors attributed those beneficial effects to the EVOO phenolic compounds and their antioxidant ability to protect against the disease‐related and age‐associated brain oxidation of these animals 8, 9, 10. More recently, it was shown that EVOO administration to a transgenic mouse model of AD‐like brain amyloidosis, TgSwDI, reduces parenchymal and vascular A β levels via an enhancement of its clearance 11…”
Section: Introductionmentioning
confidence: 99%
“…For example, recent research conducted on C57Bl/6 J mice fed with an EVOO rich in phenols (10 % EVOO weight/weight of dry diet for a daily total polyphenol dose of 6 mg/kg), showed improved contextual memory and reduced age-related impairment in motor coordination with respect to controls. While the latter effect was associated with reduced lipid peroxidation in the cerebellum, the former did not correlate with oxidation or inflammation parameters, suggesting the involvement of other mechanisms not relying on increased antioxidant protection (Pitozzi et al 2012). In support of this, are studies on the determination of the antioxidant activity of the main phenolic derivatives in human biological fluids after dietary EVOO intake, i.e.…”
Section: Introductionmentioning
confidence: 93%